Metabolic adjustment to high-altitude hypoxia: from genetic signals to physiological implications. (20th April 2018) - Murray, Andrew J.; Montgomery, Hugh E.; Feelisch, Martin; Grocott, Michael P.W.; Martin, Daniel S.
Abstract : Ascent to high altitude is associated with physiological responses that counter the stress of hypobaric hypoxia by increasing oxygen delivery and by altering tissue oxygen utilisation via metabolic modulation. At the cellular level, the transcriptional response to hypoxia is mediated by the hypoxia-inducible factor (HIF) pathway and results in promotion of glycolytic capacity and suppression of oxidative metabolism. In Tibetan highlanders, gene variants encoding components of the HIF pathway have undergone selection and are associated with adaptive phenotypic changes, including suppression of erythropoiesis and increased blood lactate levels. In some highland populations, there has also been a selection of variants in PPARA, encoding peroxisome proliferator-activated receptor alpha (PPARα), a transcriptional regulator of fatty acid metabolism. In one such population, the Sherpas, lower muscle PPARA expression is associated with a decreased capacity for fatty acid oxidation, potentially improving the efficiency of oxygen utilisation. In lowlanders ascending to altitude, a similar suppression of fatty acid oxidation occurs, although the underlying molecular mechanism appears to differ along with the consequences. Unlike lowlanders, Sherpas appear to be protected against oxidative stress and the accumulation of intramuscular lipid intermediates at altitude. Moreover, Sherpas are able to defend muscle ATP and phosphocreatine levels in the face of decreased oxygen delivery, possibly due to suppression of ATP demand pathways. The molecular mechanisms allowing Sherpas to successfully live, work and reproduce at altitude may hold the key to novel therapeutic strategies for the treatment of diseases to which hypoxia is a fundamental contributor.